Keberadaan Hukum sebagai Ilmu Pengetahuan dan Social Engineering dalam Tataran Tata Tertib Masyarakat - Tetty Melina Lubis; Arief Fahmi Lubis; Parluhutan Sagala; Tiarsen Buaton (Jurnal Pengabdian Masyarakat Waradin, 2022)
In prescriptive, legal science studies the purpose of law, the values of justice in a law, the good and bad of the rule of law, legal concepts and legal norms. While in applied science, law establishes a procedure, provisions, and limitations in enforcing a legal rule. The purpose of this study is to show that placing the law as a social phenomenon that is only viewed externally; Rather, it enters into the essence of the internal side of the law. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that in each such discourse, the question will be answered: Why is law still needed when there are already other social norms? What does the law want? In a discourse like this, legal science will open a study of legal purposes. So that what is actually going to be deal with is ideal.